Titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrodeposition and preparation method of titanium-based manganese dioxide gradient composite electrode plate
By designing a titanium-based manganese dioxide gradient composite electrode plate on the titanium-based oxide anode, the problems of easy deformation of the titanium-based oxide anode and uneven distribution of power lines are solved, and the anode life is significantly extended and the current efficiency is improved. Obtain high purity cathode products.
Patent Information
- Application Number
- CN202411381945.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-31
AI Technical Summary
Titanium-based oxide anode has problems such as easy deformation, uneven distribution of power lines, and large internal stress during the electrogenerating process of ferrous metals, resulting in short electrode life and low current efficiency.
Titanium-based manganese dioxide gradient composite electrode plates are adopted, including titanium-clad aluminum-clad conductive beams, aluminum-copper composite conductive heads, titanium-clad aluminum-clad transition titanium plates and manganese dioxide gradient composite electrode plates, and conductivity is formed through longitudinal, cross and transverse conductive reinforcement. Stents and multi-layer structures are formed on the electrode surface, such as Ta-Nb-SiOx, Mn-Sn-Ti-AgOx bottom layer, nickel-doped aluminum powder and graphene oxide α-PbO2 composite intermediate layer and γ-MnO2-TiOx composite Active layer.
The anode life is extended by 2.5 times, the tank voltage is reduced by more than 12%, the current efficiency is improved by more than 3%, and the high-purity cathode product is obtained, and the conduction efficiency and thermal oxidation life of the electrode are improved.
Smart Images

Figure CN119221045A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrodeposition and a preparation method thereof, belonging to the technical field of non-ferrous metal electrodeposition. Background Art
[0002] In the process of wet extraction of metals such as zinc, copper, nickel, cobalt, manganese, and chromium, cast lead-(0.5-1%) silver alloy is widely used as an inert anode for non-ferrous metal electrowinning due to its low cost and easy availability. Its disadvantages are: high cell voltage (3.4-3.8V), low current efficiency (75-88%), high energy consumption in the electrowinning process (3400-4200 degrees / ton of zinc), short anode service life (0.5-1 year), easy dissolution of anode lead into cathode products, resulting in a decrease in the quality of cathode products. In addition, the naturally formed oxide film is loose and easy to peel off, seriously affecting the recycling production.
[0003] Titanium-based metal oxide electrodes are insoluble anode materials with excellent electrochemical properties and electrocatalytic activity, strong corrosion resistance and long life. Although titanium has average conductivity, it has great strength and strong corrosion resistance, and is almost not corroded by most organic acids such as dilute sulfuric acid, dilute hydrochloric acid, chlorine, etc. At the same time, its mass is much smaller than that of lead plates.
[0004] At present, the research on precious metal DSA is mainly focused on the research of precious metal oxide coatings such as ruthenium and iridium. Among them, the best coating for oxygen evolution anode in electrolysis industry is IrO2-Ta2O5 composite oxide coating, which has high oxygen evolution electrocatalytic activity and electrochemical stability in aqueous solution, and can work stably in highly acidic solution and high current density. However, this type of electrode has the disadvantages of high production cost and short service life.
[0005] At present, there is a new type of inert lead dioxide anode with low cost. The preparation of this electrode usually uses titanium as the base material. Through the basic processes of base surface roughening, bottom coating, α-PbO2 intermediate layer and β-PbO2 electroplating, PbO2 electrode is plated. Its advantages are: (1) it can operate at high current density; (2) it can inhibit the formation of mud; (3) it can improve oxidation efficiency; (4) it has good corrosion resistance and long life; (5) in zinc electrowinning, it does not need chemical treatment, and the amount of lead mixed into zinc is reduced. It has good corrosion resistance to chlorine and can remove chlorine. It will not produce manganese slag and has high current efficiency for zinc extraction. However, the PbO2 electrode obtained by electroplating in this way is used as an insoluble anode, and the following problems will occur during use: (1) The PbO2 deposited layer is not tightly bonded to the electrode surface or the deposited layer is uneven; (2) The PbO2 deposited layer is easy to peel off or corrode, and its service life is not long; (3) The current efficiency is low. Although the electrocatalytic activity of the PbO2 electrode is relatively high, its current efficiency is not very high in non-ferrous metal electrowinning applications; (4) Lead ions are still produced, reducing the quality of the cathode product.
[0006] The anode plates with horizontal and vertical reinforcement rib fence-type titanium-based mesh structure have more or less problems such as insufficient plate stability, overall deformation, uneven current distribution of composite rods, and corrosion of conductive beams during use. At the same time, during use, the titanium mesh is easy to deform, the internal stress of the titanium mesh is large, and the internal stress distribution is uneven. Summary of the invention
[0007] In view of the problems existing in the current titanium-based metal oxide anodes, such as easy deformation of the titanium mesh, uneven distribution of electric lines when using the titanium mesh anode, and large internal stress, the present invention provides a titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning and a preparation method thereof. Compared with the traditional lead-calcium-tin electrolytic cell, the anode prepared by the present invention has a lifespan extended by 2.5 times, a cell voltage reduced by more than 12%, and a current efficiency increased by more than 3%, without changing the electrolytic cell structure, electrolyte composition and operating specifications, and a high-purity cathode product can be obtained.
[0008] A titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning, comprising a titanium-clad aluminum conductive beam 1, an aluminum-copper composite conductive head 2, a titanium-clad aluminum transition titanium plate 3 and a manganese dioxide gradient composite electrode plate 4, wherein the aluminum-copper composite conductive head 2 is welded and arranged at one end of the titanium-clad aluminum conductive beam 1, the titanium-clad aluminum transition titanium plate 3 is welded and arranged at the bottom end of the titanium-clad aluminum conductive beam 1, the manganese dioxide gradient composite electrode plate 4 is welded and arranged at the bottom end of the titanium-clad aluminum transition titanium plate 3, the manganese dioxide gradient composite electrode plate 4 comprises a longitudinal conductive reinforcing rib 5, a cross conductive reinforcing rib 6, a transverse conductive reinforcing rib 7 and a titanium A titanium-based manganese dioxide composite mesh plate 8, a longitudinal conductive reinforcing rib 5 is arranged on both sides of the manganese dioxide gradient composite electrode plate 4, a cross conductive reinforcing rib 6 is arranged on the diagonal of the manganese dioxide gradient composite electrode plate 4, and a transverse conductive reinforcing rib 7 is arranged at the bottom of the manganese dioxide gradient composite electrode plate 4. The longitudinal conductive reinforcing rib 5, the cross conductive reinforcing rib 6 and the transverse conductive reinforcing rib 7 form a conductive bracket, and a titanium-based manganese dioxide composite mesh plate 8 is welded in the area formed by the longitudinal conductive reinforcing rib 5, the cross conductive reinforcing rib 6 and the transverse conductive reinforcing rib 7 in the conductive bracket;
[0009] The longitudinal conductive reinforcing rib 5 includes, from the inside to the outside, a titanium-coated aluminum substrate III, an α-PbO2 composite intermediate layer I54 doped with nickel-coated aluminum powder and graphene oxide, a γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3, and a x Composite active layer I55;
[0010] The cross conductive reinforcing rib 6 includes, from the inside to the outside, a titanium-coated aluminum substrate IV, an α-PbO2 composite intermediate layer II 64 doped with nickel-coated aluminum powder and graphene oxide, a γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3, and a x Composite active layer II 65;
[0011] The transverse conductive reinforcing rib 7 includes, from the inside to the outside, a titanium-clad aluminum substrate V, an α-PbO2 composite intermediate layer V doped with nickel-clad aluminum powder and graphene oxide, a γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3, and a x Composite active layer V;
[0012] The titanium-based manganese dioxide composite mesh plate 8 includes, from the inside to the outside, a titanium mesh substrate 81, a Ta-Nb-SiOx bottom layer 82, a Mn-Sn-Ti-AgOx bottom layer 83, an α-PbO2 composite intermediate layer VI 84 doped with nickel-coated aluminum powder and graphene oxide, and a γ-MnO2-TiO2 composite intermediate layer VI 85 doped with nano-β-MnO2 and nano-Al2O3. x Composite active layer VI85.
[0013] Preferably, the titanium-clad aluminum conductive beam 1 includes, from the inside to the outside, an aluminum or aluminum alloy substrate Ⅰ11, a nickel layer Ⅰ12 and a titanium layer Ⅰ13;
[0014] The aluminum-copper composite conductive head 2 includes a copper substrate 23, a tin layer 22, and an aluminum or aluminum alloy layer 21 from the inside to the outside;
[0015] The titanium-clad aluminum transition titanium plate 3 includes an aluminum or aluminum alloy matrix II 31 , a nickel layer II 32 and a titanium layer II 33 in sequence from the inside to the outside.
[0016] Preferably, the height of the titanium-clad aluminum conductive beam 1 is 30-60 mm, the thickness is 10-40 mm, the thickness of the nickel layer I12 is 1-5 μm, and the thickness of the titanium layer I13 is 1-3 mm;
[0017] The height of the titanium-clad aluminum transition titanium plate 3 is 50-200 mm, the thickness is 4-8 mm, the thickness of the nickel layer II 32 is 0.5-3 μm, and the thickness of the titanium layer II 33 is 0.5-2 mm.
[0018] Preferably, the nickel-coated aluminum powder and graphene oxide-doped α-PbO2 composite intermediate layer has a nickel-coated aluminum powder content of 1 to 5 wt.%, a graphene oxide content of 0.1 to 0.5 wt.%, and a remainder of α-PbO2; based on the mass of the nickel-coated aluminum powder as 100%, aluminum accounts for 60 to 80 wt.%; more preferably, the aluminum is a flaky powder with a particle size of 0.5 to 5 μm; and the particle size of the graphene oxide is 10 to 100 nm;
[0019] γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 x The content of nano-β-MnO2 in the composite active layer is 0.1-2wt.%, the content of nano-Al2O3 is 0.5-5wt.%, the content of Ti is 0.1-0.5%, and the balance is γ-MnO2; more preferably, the particle size of nano-β-MnO2 is 50-100nm, and the particle size of nano-Al2O3 is 30-80nm;
[0020] Ta-Nb-SiO x The total molar amount of Ta, Nb and Si in the bottom layer is 100%, the molar amount of Ta accounts for 20-40%, the molar amount of Nb accounts for 20-40%, and the molar amount of Si accounts for 20-60%;
[0021] The total molar amount of Mn, Sn, Ti and Ag in the Mn-Sn-Ti-AgOx bottom layer is 100%, the molar amount of Mn accounts for 40-70%, the molar amount of Sn accounts for 15-25%, the molar amount of Ti accounts for 13-25%, and the molar amount of Ag accounts for 2-10%.
[0022] Preferably, the titanium-clad aluminum matrix III of the longitudinal conductive reinforcing rib 5 includes aluminum or aluminum alloy matrix from the inside to the outside.
[0023] Ⅲ51, nickel layer Ⅲ52, titanium layer Ⅲ53;
[0024] The titanium-clad aluminum substrate IV of the cross-conductive reinforcing rib 6 includes, from the inside to the outside, an aluminum or aluminum alloy substrate IV 61, a nickel layer IV 62, and a titanium layer IV 63;
[0025] The titanium-clad aluminum substrate V of the transverse conductive reinforcement rib 7 includes an aluminum or aluminum alloy substrate V, a nickel layer V, and a titanium layer V in sequence from the inside to the outside.
[0026] More preferably, the height of the longitudinal conductive reinforcing rib 5 is 10-30 mm, the thickness is 4-10 mm, the thickness of the nickel layer III 52 is 0.5-3 μm, the thickness of the titanium layer III 53 is 0.5-2 mm, the thickness of the α-PbO2 composite intermediate layer I 54 doped with nickel-coated aluminum powder and graphene oxide is 50-1000 μm, and the thickness of the γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-A12O3 is 50-1000 μm. x The composite active layer I55 has a thickness of 100 to 500 μm;
[0027] The height of the cross conductive reinforcing rib 6 is 10-30 mm, the thickness is 4-10 mm, the thickness of the nickel layer IV 62 is 0.5-3 μm, the thickness of the titanium layer IV 63 is 0.5-2 mm, the thickness of the α-PbO2 composite intermediate layer II 64 doped with nickel-coated aluminum powder and graphene oxide is 50-1000 μm, and the thickness of the γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3 is 50-1000 μm. x The thickness of the composite active layer II 65 is 100 to 500 μm;
[0028] The height of the transverse conductive reinforcing rib 7 is 10-30 mm, the thickness is 4-10 mm, the thickness of the nickel layer V is 0.5-3 μm, the thickness of the titanium layer V is 0.5-2 mm, the thickness of the α-PbO2 composite intermediate layer V doped with nickel-coated aluminum powder and graphene oxide is 50-1000 μm, and the thickness of the γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3 is 50-1000 μm. x The thickness of the composite active layer V is 100 to 500 μm;
[0029] The titanium mesh substrate 81 of the titanium-based manganese dioxide composite mesh plate 8 has a mesh long axis of 4 to 12 mm, a short axis of 2 to 8 mm, a cross-sectional thickness of 1 to 6 mm, and a Ta-Nb-SiO x The thickness of the bottom layer 82 is 1 to 5 μm, Mn-Sn-Ti-AgO x The thickness of the bottom layer 83 is 3 to 10 μm, the thickness of the α-PbO2 composite intermediate layer VI 84 doped with nickel-coated aluminum powder and graphene oxide is 50 to 1000 μm, and the thickness of the γ-MnO2-TiO x The thickness of the composite active layer VI85 is 100 to 500 μm.
[0030] The method for preparing the titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning comprises the following specific steps:
[0031] 1) Titanium mesh-based Ta-Nb-SiO x Preparation of the bottom layer: The titanium mesh substrate is successively subjected to sandblasting, leveling, degreasing (preferably, the leveled titanium mesh substrate is placed in a NaOH solution with a mass concentration of 10-20%, and degreasing at a temperature of 60-80°C for 10-30 minutes), and activation treatment (preferably, boiling activation in an oxalic acid solution with a mass concentration of 5-20% for 1-2 hours) to obtain a pretreated titanium mesh substrate, and Ta-Nb-SiO x The precursor liquid is evenly coated on the surface of the pretreated titanium mesh substrate, dried at a temperature of 80-100°C, and then sintered at a temperature of 400-700°C for 5-10 minutes. The coating of Ta-Nb-SiO is repeated 1-3 times. x The precursor liquid and sintering process are finally placed at a temperature of 400-600 ° C for 0.5-1.5 h to obtain a titanium network-based Ta-Nb-SiO x bottom layer;
[0032] 2) Titanium mesh-based Mn-Sn-Ti-AgO x Preparation of the bottom layer: Mn-Sn-Ti-AgO x The precursor liquid is evenly coated on the titanium mesh-based Ta-Nb-SiO x The surface of the bottom layer is dried at a temperature of 80 to 100 ° C, and then sintered at a temperature of 100 to 300 ° C for 8 to 10 minutes. The coating of the Mn-Sn-Ti-AgOx precursor liquid and the sintering process are repeated 8 to 12 times, and finally sintered at a temperature of 200 to 400 ° C for 1.0 to 2.0 hours to obtain a titanium mesh-based Mn-Sn-Ti-AgO x bottom layer;
[0033] 3) Assembling the titanium mesh substrate plate: The titanium-clad aluminum conductive beam and the aluminum-copper composite conductive head are welded by aluminum-aluminum friction stir welding to obtain the conductive beam; the titanium mesh base Mn-Sn-Ti-AgO x After cutting, the bottom layer is assembled and welded with the titanium-clad aluminum transition titanium plate, the titanium-clad aluminum substrate III of the cross conductive reinforcement ribs, the titanium-clad aluminum substrate IV of the cross conductive reinforcement ribs, and the titanium-clad aluminum substrate V of the transverse conductive reinforcement ribs to form a titanium mesh base plate substrate, and the titanium-clad aluminum transition titanium plate of the titanium mesh base plate substrate is welded to the bottom end of the conductive crossbeam to obtain a titanium mesh base layer plate;
[0034] 4) Preparation of α-PbO2 composite intermediate layer doped with nickel-coated aluminum powder and graphene oxide: using the titanium mesh base plate substrate of the titanium mesh base layer plate as the anode and the stainless steel plate as the cathode, electroplating in an alkaline composite lead dioxide plating solution to form an α-PbO2 composite intermediate layer doped with nickel-coated aluminum powder and graphene oxide, thereby obtaining a titanium mesh-based α-PbO2 composite electrode doped with nickel-coated aluminum powder and graphene oxide; the alkaline composite lead dioxide plating solution contains 10-60 g / L lead oxide, 100-200 g / L NaOH, 20-40 g / L lactic acid, 2-10 g / L nickel-coated aluminum powder, and 0.1-2 g / L graphene oxide;
[0035] 5)γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 x Preparation of composite active layer: Using the titanium mesh-based nickel-doped aluminum powder and graphene oxide α-PbO2 composite electrode as the anode and the titanium mesh plate as the cathode, γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 was electroplated in a manganese sulfate composite plating solution. x The composite active layer is used to obtain a titanium-based manganese dioxide gradient composite electrode plate; the manganese sulfate composite plating solution contains 50-250g / L manganese sulfate, 10-50g / L titanium sulfate, 40-150g / L sulfuric acid, 2-8g / L nano-β-MnO2, and 5-20g / L nano-Al2O3.
[0036] Preferably, in step 1) Ta-Nb-SiO x Preparation method of precursor solution: Under ultrasonic and magnetic stirring conditions, tantalum ethoxide, niobium ethoxide and tetraethyl silicate are dissolved in a mixed solvent of isopropanol and n-butanol to obtain Ta-Nb-SiO x precursor fluid;
[0037] Step 2) Mn-Sn-Ti-AgO x The preparation method of the precursor liquid is as follows: manganese nitrate and silver nitrate are dissolved in an ethanol solvent to obtain a manganese-silver mixed solution, dialkyl tin oxide and butyl titanate are dissolved in an n-butanol solvent to obtain a tin-titanium mixed solution, and the manganese-silver mixed solution is added to the tin-titanium mixed solution and stirred to obtain Mn-Sn-Ti-AgO x Precursor fluid.
[0038] Preferably, the electroplating temperature in step 4) is 40-70°C, and the anode current density is 0.5-3A / dm 2 , the electroplating time is 1 to 6 hours;
[0039] Step 5) The electroplating temperature is 85-105°C and the anode current density is 0.5-3A / dm 2 , the electroplating time is 3 to 6 hours.
[0040] Preferably, the preparation method of the nickel-coated aluminum powder in step 4) comprises the following specific steps:
[0041] The flaky aluminum powder degreased by a NaOH solution with a mass concentration of 5-10% is added to a chemical copper plating solution, and the copper-clad aluminum powder is obtained by chemically plating at a temperature of 20-40° C. for 10-30 minutes; the chemical copper plating solution contains 10-40 g / L copper sulfate, 30-80 g / L sodium citrate, 2-6 g / L sodium hydroxide, 10-30 ml / L ammonia water, and 0-5 ml / L formaldehyde solution;
[0042] The copper-clad aluminum powder is added into a dilute sulfuric acid solution with a mass concentration of 1-5% for activation to obtain activated copper-clad aluminum powder; the activated copper-clad aluminum powder is immediately added into a chemical nickel plating solution after being washed with deionized water; and the nickel-clad aluminum powder is chemically plated at a temperature of 90-100° C. for 10-90 minutes to obtain the nickel-clad aluminum powder; the chemical nickel plating solution contains 15-45 g / L nickel sulfate, 5-20 g / L sodium hypophosphite, 0.005-0.1 g / L cerium chloride, and 0.01-0.5 g / L polyethylene glycol 6000; and the pH value of the chemical nickel plating solution is 4.0-5.0.
[0043] Preferably, the preparation method of the titanium-clad aluminum conductive beam, the titanium-clad aluminum transition titanium plate, the titanium-clad aluminum substrate III of the longitudinal conductive reinforcement ribs, the titanium-clad aluminum substrate IV of the cross conductive reinforcement ribs, or the titanium-clad aluminum substrate V of the transverse conductive reinforcement ribs comprises the following specific steps:
[0044] The aluminum or aluminum alloy rod is placed in a NaOH solution with a mass concentration of 10-20%, degreased at a temperature of 50-60°C for 1-5 minutes, then washed with deionized water and placed in an alkaline zinc plating solution for 1-2 minutes, then washed with deionized water and placed in a HNO3 solution with a mass concentration of 10-20% for activation for 5-10 seconds, then placed in an alkaline zinc plating solution for a second zinc plating of 0.5-1 minute, immediately placed in a chemical nickel plating solution after washing with deionized water, and chemically plated at a temperature of 90-100°C for 30-60 minutes, The nickel-clad aluminum composite rod is washed with deionized water and then dried to obtain the nickel-clad aluminum composite rod; the alkaline zinc plating solution contains 30-80 g / L ZnO, 150-300 g / L NaOH, 10-30 g / L potassium sodium tartrate, and 1-5 g / L NaNO3; the chemical nickel plating solution contains 15-45 g / L nickel sulfate, 5-20 g / L sodium hypophosphite, 0.005-0.1 g / L cerium chloride, and 0.01-0.5 g / L polyethylene glycol 6000; the pH value of the chemical nickel plating solution is 4.0-5.0.
[0045] The inner wall of the titanium tube is roughened by a wire brush and then degreased, washed with water and placed in a HF solution with a mass concentration of 1 to 5% to remove the oxide film, washed with deionized water and then dried with hot air at a temperature of 50 to 80° C. to obtain a pretreated titanium tube;
[0046] The nickel-clad aluminum composite rod is placed in a pretreated titanium tube, extruded, drawn and composited at a rate of 1 to 4 m / min, sheared, hot rolled at a temperature of 200 to 400°C, and cooled to room temperature to obtain a titanium-clad aluminum conductive beam, a titanium-clad aluminum transition titanium plate, a titanium-clad aluminum matrix III with longitudinal conductive reinforcement ribs, a titanium-clad aluminum matrix IV with cross conductive reinforcement ribs, or a titanium-clad aluminum matrix V with transverse conductive reinforcement ribs.
[0047] Preferably, the preparation method of the aluminum-copper composite conductive head comprises the following specific steps:
[0048] The conductive copper rod is placed in a nitric acid solution with a mass concentration of 1-5% to remove the oxide film, washed with deionized water and dried, placed in a hot-dip tin solution, dip-plated at a temperature of 150-300°C for 1-5 minutes, then placed in a die-casting mold at a temperature of 100-200°C, and molten aluminum or aluminum alloy is pressed into the mold for 5-15 minutes. The desired size is milled out by a milling machine to obtain an aluminum-copper composite conductive head; the hot-dip tin solution contains 0.01-0.1% Al and the balance is Sn.
[0049] The beneficial effects of the present invention are:
[0050] (1) The titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning of the present invention has a low oxygen evolution potential, a long service life, and a high electrical efficiency. Compared with the traditional lead-calcium-tin electrolytic cell, without changing the electrolytic cell structure, electrolyte composition and operating specifications, the anode life prepared by the present invention is extended by 2.5 times, the cell voltage is reduced by more than 12%, the current efficiency is increased by more than 3%, and the cathode product quality is high;
[0051] (2) The present invention utilizes the excellent conductivity and low cost of aluminum, the high temperature oxidation resistance of nickel, and the strong corrosion resistance of titanium, and adopts a composite material of titanium-coated nickel and then aluminum-coated to greatly improve the conduction efficiency and heat-resistant oxidation life of the entire anode, reduce the cell voltage, and avoid the oxidation of aluminum at the same time;
[0052] (3) The present invention uses Ta-Nb-SiOx oxide as the first bottom layer, so that Ta and Nb form a solid solution with Ti to prevent oxidation of titanium, thereby reducing interface resistance; uses Mn-Sn-Ti-AgOx oxide as the second bottom layer, and utilizes the fewer cracks in the manganese oxide coating and the conductivity of silver to improve the conductivity of the coating and improve the conduction efficiency of the electrode;
[0053] (4) The α-PbO2 composite intermediate layer doped with nickel-coated aluminum powder and graphene oxide of the present invention reduces the internal stress of α-PbO2 by adding nickel-coated aluminum powder and graphene oxide, and also improves the conductivity of α-PbO2 and reduces the internal resistance of the electrode;
[0054] (5) The present invention adopts a sulfuric acid system to prepare a titanium-doped γ-MnO2 composite active layer, introduces active nano-β-MnO2 and nano-A12O3 with high-temperature oxidation resistance and thermal corrosion resistance; the introduction of nano-β-MnO2 improves the electrocatalytic activity of the coating, so that the entire coating has a high specific surface area during use; the synergistic effect between these particles greatly improves the electrocatalytic activity and service life of the electrode;
[0055] (6) The present invention uses transition titanium-clad aluminum plates, titanium-clad aluminum with longitudinal conductive reinforcement ribs, titanium-clad aluminum with cross conductive reinforcement ribs, and titanium-clad aluminum with transverse conductive reinforcement ribs for assembly and welding, which has high current conduction efficiency, resulting in uniform current distribution of the entire electrode plate deposition, uniform thickness of the deposited coating, and improved overall life of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 It is a schematic diagram of the structure of a titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning;
[0057] Figure 2 for Figure 1 AA cross-sectional diagram of ;
[0058] Figure 3 for Figure 1 BB cross-sectional diagram;
[0059] Figure 4 for Figure 1 Schematic diagram of CC cross section;
[0060] In the figure: 1-titanium-clad aluminum conductive beam, 11-aluminum or aluminum alloy substrate Ⅰ; 12-nickel layer Ⅰ; 13-titanium layer Ⅰ; 2-aluminum-copper composite conductive head; 21-aluminum or aluminum alloy layer; 22-tin layer; 23-copper substrate; 3-titanium-clad aluminum transition titanium plate; 31-aluminum or aluminum alloy substrate Ⅱ; 32-nickel layer Ⅱ; 33-titanium layer Ⅱ; 4-manganese dioxide gradient composite electrode plate; 5-longitudinal conductive reinforcement rib; 51-aluminum or aluminum alloy substrate Ⅲ; 52-nickel layer Ⅲ; 53-titanium layer Ⅲ; 54-α-PbO2 composite intermediate layer Ⅰ doped with nickel-clad aluminum powder and graphene oxide; 55-γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3 x Composite active layer Ⅰ; 6-cross conductive reinforcement ribs; 61-aluminum or aluminum alloy substrate Ⅳ; 62-nickel layer Ⅳ; 63-titanium layer Ⅳ; 64-α-PbO2 composite intermediate layer Ⅱ doped with nickel-coated aluminum powder and graphene oxide; 65-γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 xComposite active layer II; 7-lateral conductive reinforcement; 8-titanium-based manganese dioxide composite mesh; 81-titanium mesh substrate; 82-Ta-Nb-SiOx bottom layer; 83-Mn-Sn-Ti-AgOx bottom layer; α-PbO2 composite intermediate layer VI doped with nickel-coated aluminum powder and graphene oxide; 85-γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 x Composite active layer VI. DETAILED DESCRIPTION
[0061] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.
[0062] Summary of the Invention
[0063] A titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning, comprising a titanium-clad aluminum conductive beam 1, an aluminum-copper composite conductive head 2, a titanium-clad aluminum transition titanium plate 3 and a manganese dioxide gradient composite electrode plate 4, wherein the aluminum-copper composite conductive head 2 is welded and arranged at one end of the titanium-clad aluminum conductive beam 1, the titanium-clad aluminum transition titanium plate 3 is welded and arranged at the bottom end of the titanium-clad aluminum conductive beam 1, the manganese dioxide gradient composite electrode plate 4 is welded and arranged at the bottom end of the titanium-clad aluminum transition titanium plate 3, the manganese dioxide gradient composite electrode plate 4 comprises a longitudinal conductive reinforcing rib 5, a cross conductive reinforcing rib 6, a transverse conductive reinforcing rib 7 and a titanium A titanium-based manganese dioxide composite mesh plate 8, a longitudinal conductive reinforcing rib 5 is arranged on both sides of the manganese dioxide gradient composite electrode plate 4, a cross conductive reinforcing rib 6 is arranged on the diagonal of the manganese dioxide gradient composite electrode plate 4, and a transverse conductive reinforcing rib 7 is arranged at the bottom of the manganese dioxide gradient composite electrode plate 4. The longitudinal conductive reinforcing rib 5, the cross conductive reinforcing rib 6 and the transverse conductive reinforcing rib 7 form a conductive bracket, and a titanium-based manganese dioxide composite mesh plate 8 is welded in the area formed by the longitudinal conductive reinforcing rib 5, the cross conductive reinforcing rib 6 and the transverse conductive reinforcing rib 7 in the conductive bracket;
[0064] The longitudinal conductive reinforcing rib 5 includes, from the inside to the outside, a titanium-coated aluminum substrate III, an α-PbO2 composite intermediate layer I54 doped with nickel-coated aluminum powder and graphene oxide, a γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3, and a x Composite active layer I55;
[0065] The cross conductive reinforcing rib 6 includes, from the inside to the outside, a titanium-coated aluminum substrate IV, an α-PbO2 composite intermediate layer II 64 doped with nickel-coated aluminum powder and graphene oxide, a γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3, and a x Composite active layer II 65;
[0066] The transverse conductive reinforcing rib 7 includes, from the inside to the outside, a titanium-clad aluminum substrate V, an α-PbO2 composite intermediate layer V doped with nickel-clad aluminum powder and graphene oxide, a γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3, and a x Composite active layer V;
[0067] The titanium-based manganese dioxide composite mesh plate 8 includes, from the inside to the outside, a titanium mesh substrate 81, a Ta-Nb-SiOx bottom layer 82, a Mn-Sn-Ti-AgOx bottom layer 83, an α-PbO2 composite intermediate layer VI 84 doped with nickel-coated aluminum powder and graphene oxide, and a γ-MnO2-TiO2 composite intermediate layer VI 85 doped with nano-β-MnO2 and nano-Al2O3. x Composite active layer VI85.
[0068] The titanium-clad aluminum conductive beam 1 includes, from the inside to the outside, an aluminum or aluminum alloy substrate Ⅰ11, a nickel layer Ⅰ12 and a titanium layer Ⅰ13;
[0069] The aluminum-copper composite conductive head 2 includes a copper substrate 23, a tin layer 22, and an aluminum or aluminum alloy layer 21 from the inside to the outside;
[0070] The titanium-clad aluminum transition titanium plate 3 includes an aluminum or aluminum alloy matrix II 31 , a nickel layer II 32 and a titanium layer II 33 in sequence from the inside to the outside.
[0071] The height of the titanium-clad aluminum conductive beam 1 is 30-60 mm, the thickness is 10-40 mm, the thickness of the nickel layer I12 is 1-5 μm, and the thickness of the titanium layer I13 is 1-3 mm;
[0072] The height of the titanium-clad aluminum transition titanium plate 3 is 50-200 mm, the thickness is 4-8 mm, the thickness of the nickel layer II 32 is 0.5-3 μm, and the thickness of the titanium layer II 33 is 0.5-2 mm.
[0073] The α-PbO2 composite intermediate layer doped with nickel-coated aluminum powder and graphene oxide has a nickel-coated aluminum powder content of 1 to 5 wt.%, a graphene oxide content of 0.1 to 0.5 wt.%, and a balance of α-PbO2; based on the mass of the nickel-coated aluminum powder being 100%, aluminum accounts for 60 to 80 wt.%; more preferably, the aluminum is a flaky powder with a particle size of 0.5 to 5 μm; and the particle size of the graphene oxide is 10 to 100 nm;
[0074] γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 x The content of nano-β-MnO2 in the composite active layer is 0.1-2wt.%, the content of nano-Al2O3 is 0.5-5wt.%, the content of Ti is 0.1-0.5%, and the balance is γ-MnO2; more preferably, the particle size of nano-β-MnO2 is 50-100nm, and the particle size of nano-Al2O3 is 30-80nm;
[0075] Ta-Nb-SiO x The total molar amount of Ta, Nb and Si in the bottom layer is 100%, the molar amount of Ta accounts for 20-40%, the molar amount of Nb accounts for 20-40%, and the molar amount of Si accounts for 20-60%;
[0076] The total molar amount of Mn, Sn, Ti and Ag in the Mn-Sn-Ti-AgOx bottom layer is 100%, the molar amount of Mn accounts for 40-70%, the molar amount of Sn accounts for 15-25%, the molar amount of Ti accounts for 13-25%, and the molar amount of Ag accounts for 2-10%.
[0077] The titanium-clad aluminum substrate III of the longitudinal conductive reinforcing rib 5 includes, from the inside to the outside, an aluminum or aluminum alloy substrate III51, a nickel layer III52, and a titanium layer III53;
[0078] The titanium-clad aluminum substrate IV of the cross-conductive reinforcing rib 6 includes, from the inside to the outside, an aluminum or aluminum alloy substrate IV 61, a nickel layer IV 62, and a titanium layer IV 63;
[0079] The titanium-clad aluminum substrate V of the transverse conductive reinforcement rib 7 includes an aluminum or aluminum alloy substrate V, a nickel layer V, and a titanium layer V in sequence from the inside to the outside.
[0080] The height of the longitudinal conductive reinforcing rib 5 is 10-30 mm, the thickness is 4-10 mm, the thickness of the nickel layer III 52 is 0.5-3 μm, the thickness of the titanium layer III 53 is 0.5-2 mm, the thickness of the α-PbO2 composite intermediate layer I 54 doped with nickel-coated aluminum powder and graphene oxide is 50-1000 μm, and the thickness of the γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-A12O3 is 50-1000 μm. x The composite active layer I55 has a thickness of 100 to 500 μm;
[0081] The height of the cross conductive reinforcing rib 6 is 10-30 mm, the thickness is 4-10 mm, the thickness of the nickel layer IV 62 is 0.5-3 μm, the thickness of the titanium layer IV 63 is 0.5-2 mm, the thickness of the α-PbO2 composite intermediate layer II 64 doped with nickel-coated aluminum powder and graphene oxide is 50-1000 μm, and the thickness of the γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3 is 50-1000 μm. x The thickness of the composite active layer II 65 is 100 to 500 μm;
[0082] The height of the transverse conductive reinforcing rib 7 is 10-30 mm, the thickness is 4-10 mm, the thickness of the nickel layer V is 0.5-3 μm, the thickness of the titanium layer V is 0.5-2 mm, the thickness of the α-PbO2 composite intermediate layer V doped with nickel-coated aluminum powder and graphene oxide is 50-1000 μm, and the thickness of the γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3 is 50-1000 μm. x The thickness of the composite active layer V is 100 to 500 μm;
[0083] The titanium mesh substrate 81 of the titanium-based manganese dioxide composite mesh plate 8 has a mesh long axis of 4 to 12 mm, a short axis of 2 to 8 mm, a cross-sectional thickness of 1 to 6 mm, and a Ta-Nb-SiO x The thickness of the bottom layer 82 is 1 to 5 μm, Mn-Sn-Ti-AgO x The thickness of the bottom layer 83 is 3 to 10 μm, the thickness of the α-PbO2 composite intermediate layer VI 84 doped with nickel-coated aluminum powder and graphene oxide is 50 to 1000 μm, and the thickness of the γ-MnO2-TiO x The thickness of the composite active layer VI85 is 100 to 500 μm.
[0084] The method for preparing the titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning comprises the following specific steps:
[0085] 1) Titanium mesh-based Ta-Nb-SiO x Preparation of the bottom layer: The titanium mesh substrate is successively subjected to sandblasting, leveling, degreasing (preferably, the leveled titanium mesh substrate is placed in a NaOH solution with a mass concentration of 10-20%, and degreasing at a temperature of 60-80°C for 10-30 minutes), and activation treatment (preferably, boiling activation in an oxalic acid solution with a mass concentration of 5-20% for 1-2 hours) to obtain a pretreated titanium mesh substrate, and Ta-Nb-SiO x The precursor liquid is evenly coated on the surface of the pretreated titanium mesh substrate, dried at a temperature of 80-100°C, and then sintered at a temperature of 400-700°C for 5-10 minutes. The coating of Ta-Nb-SiO is repeated 1-3 times. x The precursor liquid and sintering process are finally placed at a temperature of 400-600 ° C for 0.5-1.5 h to obtain a titanium network-based Ta-Nb-SiO x Bottom layer: the Ta-Nb-SiO x Preparation method of precursor solution: Under ultrasonic and magnetic stirring conditions, tantalum ethoxide, niobium ethoxide and tetraethyl silicate are dissolved in a mixed solvent of isopropanol and n-butanol to obtain Ta-Nb-SiO x precursor fluid;
[0086] 2) Titanium mesh-based Mn-Sn-Ti-AgO x Preparation of the bottom layer: Mn-Sn-Ti-AgO x The precursor liquid is evenly coated on the titanium mesh-based Ta-Nb-SiO x The surface of the bottom layer is dried at a temperature of 80 to 100 ° C, and then sintered at a temperature of 100 to 300 ° C for 8 to 10 minutes. The coating of the Mn-Sn-Ti-AgOx precursor liquid and the sintering process are repeated 8 to 12 times, and finally sintered at a temperature of 200 to 400 ° C for 1.0 to 2.0 hours to obtain a titanium mesh-based Mn-Sn-Ti-AgOx Bottom layer: the Mn-Sn-Ti-AgO x The preparation method of the precursor liquid is as follows: manganese nitrate and silver nitrate are dissolved in an ethanol solvent to obtain a manganese-silver mixed solution, dialkyl tin oxide and butyl titanate are dissolved in an n-butanol solvent to obtain a tin-titanium mixed solution, and the manganese-silver mixed solution is added to the tin-titanium mixed solution and stirred to obtain Mn-Sn-Ti-AgO x precursor fluid;
[0087] 3) Assembling the titanium mesh substrate plate: The titanium-clad aluminum conductive beam and the aluminum-copper composite conductive head are welded by aluminum-aluminum friction stir welding to obtain the conductive beam; the titanium mesh base Mn-Sn-Ti-AgO x After cutting, the bottom layer is assembled and welded with the titanium-clad aluminum transition titanium plate, the titanium-clad aluminum substrate III of the cross conductive reinforcement ribs, the titanium-clad aluminum substrate IV of the cross conductive reinforcement ribs, and the titanium-clad aluminum substrate V of the transverse conductive reinforcement ribs to form a titanium mesh base plate substrate, and the titanium-clad aluminum transition titanium plate of the titanium mesh base plate substrate is welded to the bottom end of the conductive beam to obtain a titanium mesh base layer plate; the preparation method of the titanium-clad aluminum conductive beam, the titanium-clad aluminum transition titanium plate, the titanium-clad aluminum substrate III of the longitudinal conductive reinforcement ribs, the titanium-clad aluminum substrate IV of the cross conductive reinforcement ribs, or the titanium-clad aluminum substrate V of the transverse conductive reinforcement ribs, the specific steps are as follows:
[0088] The aluminum or aluminum alloy rod is placed in a NaOH solution with a mass concentration of 10-20%, degreased at a temperature of 50-60°C for 1-5 minutes, then washed with deionized water and placed in an alkaline zinc plating solution for 1-2 minutes, then washed with deionized water and placed in a HNO3 solution with a mass concentration of 10-20% for activation for 5-10 seconds, then placed in an alkaline zinc plating solution for a second zinc plating of 0.5-1 minute, immediately placed in a chemical nickel plating solution after washing with deionized water, and chemically plated at a temperature of 90-100°C for 30-60 minutes, The nickel-clad aluminum composite rod is washed with deionized water and then dried to obtain the nickel-clad aluminum composite rod; the alkaline zinc plating solution contains 30-80 g / L ZnO, 150-300 g / L NaOH, 10-30 g / L potassium sodium tartrate, and 1-5 g / L NaNO3; the chemical nickel plating solution contains 15-45 g / L nickel sulfate, 5-20 g / L sodium hypophosphite, 0.005-0.1 g / L cerium chloride, and 0.01-0.5 g / L polyethylene glycol 6000; the pH value of the chemical nickel plating solution is 4.0-5.0.
[0089] The inner wall of the titanium tube is roughened by a wire brush and then degreased, washed with water and placed in a HF solution with a mass concentration of 1 to 5% to remove the oxide film, washed with deionized water and then dried with hot air at a temperature of 50 to 80° C. to obtain a pretreated titanium tube;
[0090] The nickel-clad aluminum composite rod is placed in a pretreated titanium tube, extruded and drawn at a rate of 1 to 4 m / min, sheared, hot rolled at a temperature of 200 to 400° C., and cooled to room temperature to obtain a titanium-clad aluminum conductive beam, a titanium-clad aluminum transition titanium plate, a titanium-clad aluminum matrix III with longitudinal conductive reinforcement ribs, a titanium-clad aluminum matrix IV with cross conductive reinforcement ribs, or a titanium-clad aluminum matrix V with transverse conductive reinforcement ribs;
[0091] The preparation method of the aluminum-copper composite conductive head comprises the following specific steps:
[0092] The conductive copper rod is placed in a nitric acid solution with a mass concentration of 1-5% to remove the oxide film, washed with deionized water and dried, placed in a hot-dip tin solution, dip-plated at a temperature of 150-300°C for 1-5 minutes, and then placed in a die-casting mold at a temperature of 100-200°C, and molten aluminum or aluminum alloy is pressed into the mold for 5-15 minutes, and milled out to the required size by a milling machine to obtain an aluminum-copper composite conductive head; the hot-dip tin solution contains 0.01-0.1% Al and the balance is Sn;
[0093] 4) Preparation of α-PbO2 composite intermediate layer doped with nickel-coated aluminum powder and graphene oxide: using the titanium mesh base plate substrate of the titanium mesh base layer plate as the anode and the stainless steel plate as the cathode, electroplating in an alkaline composite lead dioxide plating solution to form an α-PbO2 composite intermediate layer doped with nickel-coated aluminum powder and graphene oxide, thereby obtaining a titanium mesh-based α-PbO2 composite electrode doped with nickel-coated aluminum powder and graphene oxide; the alkaline composite lead dioxide plating solution contains 10-60 g / L lead oxide, 100-200 g / L NaOH, 20-40 g / L lactic acid, 2-10 g / L nickel-coated aluminum powder, and 0.1-2 g / L graphene oxide; the electroplating temperature is 40-70°C, and the anode current density is 0.5-3 A / dm 2 , the electroplating time is 1 to 6 hours;
[0094] The preparation method of the nickel-coated aluminum powder comprises the following specific steps:
[0095] The flaky aluminum powder degreased by a NaOH solution with a mass concentration of 5-10% is added to a chemical copper plating solution, and the copper-clad aluminum powder is obtained by chemically plating at a temperature of 20-40° C. for 10-30 minutes; the chemical copper plating solution contains 10-40 g / L copper sulfate, 30-80 g / L sodium citrate, 2-6 g / L sodium hydroxide, 10-30 ml / L ammonia water, and 0-5 ml / L formaldehyde solution;
[0096] The copper-clad aluminum powder is added to a dilute sulfuric acid solution with a mass concentration of 1-5% to activate the activated copper-clad aluminum powder, and the activated copper-clad aluminum powder is immediately added to a chemical nickel plating solution after being washed with deionized water, and chemically plated at a temperature of 90-100° C. for 10-90 minutes to obtain nickel-clad aluminum powder; the chemical nickel plating solution contains 15-45 g / L nickel sulfate, 5-20 g / L sodium hypophosphite, 0.005-0.1 g / L cerium chloride, and 0.01-0.5 g / L polyethylene glycol 6000, and the pH of the chemical nickel plating solution is 4.0-5.0;
[0097] 5)γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 x Preparation of composite active layer: Using the titanium mesh-based nickel-doped aluminum powder and graphene oxide α-PbO2 composite electrode as the anode and the titanium mesh plate as the cathode, γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 was electroplated in a manganese sulfate composite plating solution. x The composite active layer is used to obtain a titanium-based manganese dioxide gradient composite electrode plate; the manganese sulfate composite plating solution contains 50-250 g / L manganese sulfate, 10-50 g / L titanium sulfate, 40-150 g / L sulfuric acid, 2-8 g / L nano β-MnO2, and 5-20 g / L nano Al2O3; the electroplating temperature is 85-105°C, and the anode current density is 0.5-3 A / dm 2 , the electroplating time is 3 to 6 hours.
[0098] Example 1: This example is a titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning (see Figures 1 to 4 ), comprising a titanium-clad aluminum conductive beam 1, an aluminum-copper composite conductive head 2, a titanium-clad aluminum transition titanium plate 3 and a manganese dioxide gradient composite electrode plate 4, wherein the aluminum-copper composite conductive head 2 is welded and arranged at one end of the titanium-clad aluminum conductive beam 1, a titanium-clad aluminum transition titanium plate 3 is welded and arranged at the bottom end of the titanium-clad aluminum conductive beam 1, a manganese dioxide gradient composite electrode plate 4 is welded and arranged at the bottom end of the titanium-clad aluminum transition titanium plate 3, the manganese dioxide gradient composite electrode plate 4 comprises a longitudinal conductive reinforcement rib 5, a cross conductive reinforcement rib 6, a transverse conductive reinforcement rib 7 and a titanium-based manganese dioxide composite mesh plate 8, the longitudinal conductive reinforcement rib 5 is arranged on both sides of the manganese dioxide gradient composite electrode plate 4, the cross conductive reinforcement rib 6 is arranged on the diagonal line of the manganese dioxide gradient composite electrode plate 4, the transverse conductive reinforcement rib 7 is arranged at the bottom end of the manganese dioxide gradient composite electrode plate 4, the longitudinal conductive reinforcement rib 5, the cross conductive reinforcement rib 6 and the transverse conductive reinforcement rib 7 constitute a conductive bracket, and the titanium-based manganese dioxide composite mesh plate 8 is welded and arranged in the area divided by the longitudinal conductive reinforcement rib 5, the cross conductive reinforcement rib 6 and the transverse conductive reinforcement rib 7 in the conductive bracket;
[0099] The longitudinal conductive reinforcing rib 5 includes, from the inside to the outside, a titanium-coated aluminum substrate III, an α-PbO2 composite intermediate layer I54 doped with nickel-coated aluminum powder and graphene oxide, a γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3, and a x Composite active layer Ⅰ55; the titanium-clad aluminum substrate Ⅲ includes an aluminum substrate Ⅲ51, a nickel layer Ⅲ52, and a titanium layer Ⅲ53 from the inside to the outside;
[0100] The cross conductive reinforcing rib 6 includes, from the inside to the outside, a titanium-coated aluminum substrate IV, an α-PbO2 composite intermediate layer II 64 doped with nickel-coated aluminum powder and graphene oxide, a γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3, and a x Composite active layer II 65; the titanium-clad aluminum substrate IV includes, from inside to outside, an aluminum substrate IV 61, a nickel layer IV 62, and a titanium layer IV 63;
[0101] The transverse conductive reinforcing rib 7 includes, from the inside to the outside, a titanium-clad aluminum substrate V, an α-PbO2 composite intermediate layer V doped with nickel-clad aluminum powder and graphene oxide, a γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3, and a x Composite active layer V; the titanium-clad aluminum substrate V comprises, from inside to outside, an aluminum substrate V, a nickel layer V, and a titanium layer V;
[0102] The titanium-based manganese dioxide composite mesh plate 8 includes, from the inside to the outside, a titanium mesh substrate 81, a Ta-Nb-SiOx bottom layer 82, a Mn-Sn-Ti-AgOx bottom layer 83, an α-PbO2 composite intermediate layer VI 84 doped with nickel-coated aluminum powder and graphene oxide, and a γ-MnO2-TiO2 composite intermediate layer VI 85 doped with nano-β-MnO2 and nano-Al2O3. x Composite active layer VI85;
[0103] The titanium-clad aluminum conductive beam 1 includes an aluminum substrate Ⅰ11, a nickel layer Ⅰ12 and a titanium layer Ⅰ13 from the inside to the outside;
[0104] The aluminum-copper composite conductive head 2 includes a copper substrate 23, a tin layer 22, and an aluminum layer 21 from the inside to the outside;
[0105] The titanium-clad aluminum transition titanium plate 3 includes an aluminum substrate II 31, a nickel layer II 32 and a titanium layer II 33 from the inside to the outside;
[0106] The titanium-clad aluminum conductive beam 1 has a height of 30 mm and a thickness of 10 mm, a nickel layer Ⅰ12 has a thickness of 1 μm, and a titanium layer Ⅰ13 has a thickness of 1 mm;
[0107] The height of the titanium-clad aluminum transition titanium plate 3 is 5 mm, the thickness is 4 mm, the thickness of the nickel layer II 32 is 0.5 μm, and the thickness of the titanium layer II 33 is 0.5 mm;
[0108] The α-PbO2 composite intermediate layer doped with nickel-coated aluminum powder and graphene oxide has a nickel-coated aluminum powder content of 1wt.%, a graphene oxide content of 0.1wt.% (the particle size of graphene oxide is 10nm), and the remainder is α-PbO2; based on the mass of the nickel-coated aluminum powder being 100%, aluminum (aluminum is a flaky powder with a particle size of 0.5μm) accounts for 60wt.%;
[0109] γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 x The content of nano-β-MnO2 (the particle size of nano-β-MnO2 is 50nm) in the composite active layer is 0.1wt.%, the content of nano-Al2O3 (the particle size of nano-Al2O3 is 30nm) is 0.5wt.%, the content of Ti is 0.1%, and the balance is γ-MnO2;
[0110] Ta-Nb-SiO x The total molar amount of Ta, Nb and Si in the bottom layer is 100%, the molar amount of Ta accounts for 20%, the molar amount of Nb accounts for 20%, and the molar amount of Si accounts for 60%;
[0111] The total molar amount of Mn, Sn, Ti and Ag in the Mn-Sn-Ti-AgOx bottom layer is 100%, the molar amount of Mn accounts for 40%, the molar amount of Sn accounts for 25%, the molar amount of Ti accounts for 25%, and the molar amount of Ag accounts for 10%;
[0112] The height of the longitudinal conductive reinforcing rib 5 is 30 mm, the thickness is 10 mm, the thickness of the nickel layer III 52 is 1 μm, the thickness of the titanium layer III 53 is 1 mm, the thickness of the α-PbO2 composite intermediate layer I 54 doped with nickel-coated aluminum powder and graphene oxide is 50 μm, and the thickness of the γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-A12O3 is 50 μm. x The thickness of the composite active layer I55 is 100 μm;
[0113] The height of the cross conductive reinforcement rib 6 is 30 mm, the thickness is 10 mm, the thickness of the nickel layer IV 62 is 1 μm, the thickness of the titanium layer IV 63 is 1 mm, the thickness of the α-PbO2 composite intermediate layer II 64 doped with nickel-coated aluminum powder and graphene oxide is 50 μm, and the thickness of the γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3 is 50 μm. x The thickness of the composite active layer II65 is 100 μm;
[0114] The height of the transverse conductive reinforcing rib 7 is 30 mm, the thickness is 10 mm, the thickness of the nickel layer V is 1 μm, the thickness of the titanium layer V is 1 mm, the thickness of the α-PbO2 composite intermediate layer V doped with nickel-coated aluminum powder and graphene oxide is 50 μm, and the thickness of the γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3 is 50 μm. x The thickness of the composite active layer V is 100 μm;
[0115] The titanium mesh substrate 81 of the titanium-based manganese dioxide composite mesh plate 8 is TA1 alloy, the mesh long axis is 4 mm, the short axis is 2 mm, the cross-sectional thickness is 1 mm, and the Ta-Nb-SiO x The bottom layer 82 has a thickness of 1 μm and is composed of Mn-Sn-Ti-AgO x The thickness of the bottom layer 83 is 3 μm, the thickness of the α-PbO2 composite intermediate layer VI 84 doped with nickel-coated aluminum powder and graphene oxide is 50 μm, and the thickness of the γ-MnO2-TiO x The composite active layer VI85 has a thickness of 100 μm;
[0116] A method for preparing a titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning, the specific steps are as follows:
[0117] 1) Titanium mesh-based Ta-Nb-SiO x Preparation of the bottom layer: The titanium mesh substrate was sandblasted and leveled at 400°C, then placed in a 10% NaOH solution, degreased at 60°C for 10 min, and then placed in a 5% oxalic acid solution for boiling activation for 1 h, washed with deionized water, and dried with hot air to obtain a pretreated titanium mesh substrate. x The precursor liquid is evenly coated on the surface of the pretreated titanium mesh substrate, dried at 80 °C, and then sintered at 400 °C for 5 min. The coating of Ta-Nb-SiO x The precursor liquid and sintering process, and finally sintered at 400 ° C for 0.5 h to obtain the titanium network-based Ta-Nb-SiO x Bottom layer: the Ta-Nb-SiO x Preparation method of precursor solution: Under ultrasonic and magnetic stirring conditions, tantalum ethoxide, niobium ethoxide and tetraethyl silicate are dissolved in a mixed solvent of isopropanol and n-butanol to obtain Ta-Nb-SiO x precursor fluid;
[0118] 2) Titanium mesh-based Mn-Sn-Ti-AgO x Preparation of the bottom layer: Mn-Sn-Ti-AgO x The precursor liquid is evenly coated on the titanium mesh-based Ta-Nb-SiO x The bottom surface was dried at 80 °C, and then sintered at 100 °C for 8 min. The coating of Mn-Sn-Ti-AgOx precursor liquid and the sintering process were repeated 8 times, and finally sintered at 200 °C for 1.0 h to obtain a titanium mesh-based Mn-Sn-Ti-AgO x Bottom layer: the Mn-Sn-Ti-AgO xThe preparation method of the precursor liquid is as follows: manganese nitrate and silver nitrate are dissolved in an ethanol solvent to obtain a manganese-silver mixed solution, dialkyl tin oxide and butyl titanate are dissolved in an n-butanol solvent to obtain a tin-titanium mixed solution, and the manganese-silver mixed solution is added to the tin-titanium mixed solution and stirred to obtain Mn-Sn-Ti-AgO x precursor fluid;
[0119] 3) Assembling the titanium mesh substrate plate: The titanium-clad aluminum conductive beam and the aluminum-copper composite conductive head are welded by aluminum-aluminum friction stir welding to obtain the conductive beam; the titanium mesh base Mn-Sn-Ti-AgO x After cutting, the bottom layer is assembled and welded with the titanium-clad aluminum transition titanium plate, the titanium-clad aluminum substrate III of the cross conductive reinforcement ribs, the titanium-clad aluminum substrate IV of the cross conductive reinforcement ribs, and the titanium-clad aluminum substrate V of the transverse conductive reinforcement ribs to form a titanium mesh base plate substrate, and the titanium-clad aluminum transition titanium plate of the titanium mesh base plate substrate is welded to the bottom end of the conductive crossbeam to obtain a titanium mesh base layer plate;
[0120] The preparation method of the titanium-clad aluminum conductive beam, the titanium-clad aluminum transition titanium plate, the titanium-clad aluminum substrate III of the longitudinal conductive reinforcement ribs, the titanium-clad aluminum substrate IV of the cross conductive reinforcement ribs, or the titanium-clad aluminum substrate V of the transverse conductive reinforcement ribs comprises the following specific steps:
[0121] (a) placing an aluminum rod in a 10% NaOH solution, degreasing it at 50°C for 1 min, then washing it with deionized water and dipping it in an alkaline zinc plating solution for 1 min, washing it with deionized water and activating it in a 10% HNO3 solution for 5 s, dipping it in the alkaline zinc plating solution for a second zinc plating for 0.5 min, immediately placing it in a chemical nickel plating solution after washing it with deionized water, chemically plating it at 90°C for 30 min, washing it with deionized water and drying it to obtain a nickel-clad aluminum composite rod; the alkaline zinc plating solution contains 30 g / L ZnO, 150 g / L NaOH, 10 g / L potassium sodium tartrate, and 1 g / L NaNO3; the chemical nickel plating solution contains 15 g / L nickel sulfate, 15 g / L sodium hypophosphite, 0.005 g / L cerium chloride, and 0.01 g / L polyethylene glycol 6000; the pH of the chemical nickel plating solution is 4.0;
[0122] (b) The inner wall of the titanium tube is roughened by a wire brush and then degreased, washed with water and placed in a 1% HF solution to remove the oxide film, washed with deionized water and dried with hot air at 50° C. to obtain a pretreated titanium tube;
[0123] (c) placing the nickel-clad aluminum composite rod in a pretreated titanium tube, extruding and drawing the composite rod at a rate of 1 m / min, shearing, hot rolling at a temperature of 200° C., and cooling to room temperature to obtain a titanium-clad aluminum conductive beam, a titanium-clad aluminum transition titanium plate, a titanium-clad aluminum substrate III with longitudinal conductive reinforcement ribs, a titanium-clad aluminum substrate IV with cross conductive reinforcement ribs, or a titanium-clad aluminum substrate V with transverse conductive reinforcement ribs;
[0124] The preparation method of the aluminum-copper composite conductive head comprises the following specific steps:
[0125] The conductive copper rod is placed in a nitric acid solution with a mass concentration of 1%, the oxide film is removed, the rod is washed with deionized water, and then dried. The rod is placed in a hot-dip tin solution, and is dip-plated at a temperature of 150°C for 1 minute. The rod is then placed in a die-casting mold at a temperature of 100°C, and molten aluminum is pressed into the mold for 5 minutes. The rod is milled out to the required size using a milling machine to obtain an aluminum-copper composite conductive head. The hot-dip tin solution contains 0.01% Al and the remainder is Sn.
[0126] 4) Preparation of α-PbO2 composite intermediate layer doped with nickel-coated aluminum powder and graphene oxide: The titanium mesh base plate substrate of the titanium mesh base layer plate is used as the anode and the stainless steel plate is used as the cathode. The plate is placed in an alkaline composite lead dioxide plating solution at a temperature of 40°C and an anode current density of 0.5A / dm 2 Under the conditions, electroplating for 1 hour forms an α-PbO2 composite intermediate layer doped with nickel-coated aluminum powder and graphene oxide, thereby obtaining a titanium mesh-based α-PbO2 composite electrode doped with nickel-coated aluminum powder and graphene oxide; the alkaline composite lead dioxide plating solution contains 10g / L lead oxide, 100g / L NaOH, 20g / L lactic acid, 2g / L nickel-coated aluminum powder, and 0.1g / L graphene oxide;
[0127] The preparation method of the nickel-coated aluminum powder comprises the following specific steps:
[0128] (a) adding flaky aluminum powder degreased by a 5% NaOH solution to an electroless copper plating solution, and electroplating for 10 min at a temperature of 20° C. to obtain copper-clad aluminum powder; the electroless copper plating solution contains 10 g / L copper sulfate, 30 g / L sodium citrate, 2 g / L sodium hydroxide, and 10 ml / L ammonia water;
[0129] (b) adding copper-clad aluminum powder to a dilute sulfuric acid solution with a mass concentration of 1% to activate the activated copper-clad aluminum powder, washing the activated copper-clad aluminum powder with deionized water and immediately adding it to a chemical nickel plating solution, and chemically plating it at a temperature of 90° C. for 10 minutes to obtain nickel-clad aluminum powder; the chemical nickel plating solution contains 15 g / L nickel sulfate, 15 g / L sodium hypophosphite, 0.005 g / L cerium chloride, and 0.01 g / L polyethylene glycol 6000, and the pH of the chemical nickel plating solution is 4.0;
[0130] 5)γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 x Preparation of composite active layer: The α-PbO2 composite electrode doped with nickel-coated aluminum powder and graphene oxide on titanium mesh was used as the anode and the titanium mesh plate was used as the cathode. The composite active layer was placed in a manganese sulfate composite plating solution at a temperature of 85°C and an anode current density of 0.5A / dm 2Under the conditions, γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 was formed by electroplating for 3h. x The composite active layer is obtained to obtain a titanium-based manganese dioxide gradient composite electrode plate; the manganese sulfate composite plating solution contains 50g / L manganese sulfate, 10g / L titanium sulfate, 40g / L sulfuric acid, 2g / L nano β-MnO2, and 5g / L nano Al2O3;
[0131] The titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning prepared in this embodiment is placed in a zinc electrolyte under the following electrolysis conditions: the electrolyte is 50 g / L Zn 2+ +150g / LH2SO4+800mg / LCl-, solution temperature is 35℃; anode current density is 500A / m 2 Compared with the Pb-0.5% Ag alloy anode plate, without changing the electrolytic cell structure, electrolyte composition and operating specifications, the anode life is extended by 2.5 times, the cell voltage is reduced by more than 12%, the current efficiency is increased by more than 3%, and the cathode product can be obtained by # The zinc purity can reach over 93%.
[0132] Example 2: The titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning in this example is basically the same in structure as the titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning in Example 1, except that:
[0133] The longitudinal conductive reinforcing rib 5 includes, from the inside to the outside, a titanium-coated aluminum substrate III, an α-PbO2 composite intermediate layer I54 doped with nickel-coated aluminum powder and graphene oxide, a γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3, and a x Composite active layer Ⅰ55; the titanium-clad aluminum substrate Ⅲ includes, from the inside to the outside, an aluminum alloy substrate Ⅲ51, a nickel layer Ⅲ52, and a titanium layer Ⅲ53;
[0134] The cross conductive reinforcing rib 6 includes, from the inside to the outside, a titanium-coated aluminum substrate IV, an α-PbO2 composite intermediate layer II 64 doped with nickel-coated aluminum powder and graphene oxide, a γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3, and a x Composite active layer II 65; the titanium-clad aluminum substrate IV includes, from the inside to the outside, an aluminum alloy substrate IV 61, a nickel layer IV 62, and a titanium layer IV 63;
[0135] The transverse conductive reinforcing rib 7 includes, from the inside to the outside, a titanium-clad aluminum substrate V, an α-PbO2 composite intermediate layer V doped with nickel-clad aluminum powder and graphene oxide, a γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3, and a x Composite active layer V; the titanium-clad aluminum substrate V comprises, from inside to outside, an aluminum alloy substrate V, a nickel layer V, and a titanium layer V;
[0136] The titanium-based manganese dioxide composite mesh plate 8 includes, from the inside to the outside, a titanium mesh substrate 81, a Ta-Nb-SiOx bottom layer 82, a Mn-Sn-Ti-AgOx bottom layer 83, an α-PbO2 composite intermediate layer VI 84 doped with nickel-coated aluminum powder and graphene oxide, and a γ-MnO2-TiO2 composite intermediate layer VI 85 doped with nano-β-MnO2 and nano-Al2O3. x Composite active layer VI85;
[0137] The titanium-clad aluminum conductive beam 1 includes an aluminum alloy substrate Ⅰ11, a nickel layer Ⅰ12 and a titanium layer Ⅰ13 from the inside to the outside;
[0138] The aluminum-copper composite conductive head 2 includes a copper substrate 23, a tin layer 22, and an aluminum alloy layer 21 from the inside to the outside.
[0139] The titanium-clad aluminum transition titanium plate 3 includes an aluminum alloy substrate II 31, a nickel layer II 32 and a titanium layer II 33 from the inside to the outside;
[0140] The height of the titanium-clad aluminum conductive beam 1 is 60 mm, the thickness is 40 mm, the thickness of the nickel layer I12 is 5 μm, and the thickness of the titanium layer I13 is 3 mm;
[0141] The height of the titanium-clad aluminum transition titanium plate 3 is 200 mm, the thickness is 8 mm, the thickness of the nickel layer II 32 is 3 μm, and the thickness of the titanium layer II 33 is 2 mm;
[0142] The α-PbO2 composite intermediate layer doped with nickel-coated aluminum powder and graphene oxide has a nickel-coated aluminum powder content of 5wt.%, a graphene oxide content of 0.5wt.% (the particle size of the graphene oxide is 100nm), and a balance of α-PbO2; based on the mass of the nickel-coated aluminum powder being 100%, aluminum (aluminum is a flaky powder with a particle size of 5μm) accounts for 80wt.%;
[0143] γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 x The composite active layer contains 2wt.% of nano-β-MnO2 (the particle size of nano-β-MnO2 is 100nm), 5wt.% of nano-Al2O3 (the particle size of nano-Al2O3 is 80nm), 0.5% of Ti, and the balance is γ-MnO2;
[0144] Ta-Nb-SiO x The total molar amount of Ta, Nb and Si in the bottom layer is 100%, the molar amount of Ta accounts for 40%, the molar amount of Nb accounts for 40%, and the molar amount of Si accounts for 20%;
[0145] The total molar amount of Mn, Sn, Ti and Ag in the Mn-Sn-Ti-AgOx bottom layer is 100%, the molar amount of Mn accounts for 70%, the molar amount of Sn accounts for 15%, the molar amount of Ti accounts for 13%, and the molar amount of Ag accounts for 2%;
[0146] The height of the longitudinal conductive reinforcing rib 5 is 30 mm, the thickness is 10 mm, the thickness of the nickel layer III 52 is 3 μm, the thickness of the titanium layer III 53 is 2 mm, the thickness of the α-PbO2 composite intermediate layer I 54 doped with nickel-coated aluminum powder and graphene oxide is 1000 μm, and the thickness of the γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-A12O3 is 1000 μm. x The thickness of the composite active layer I55 is 500 μm;
[0147] The height of the cross conductive reinforcement rib 6 is 30 mm, the thickness is 10 mm, the thickness of the nickel layer IV 62 is 3 μm, the thickness of the titanium layer IV 63 is 2 mm, the thickness of the α-PbO2 composite intermediate layer II 64 doped with nickel-coated aluminum powder and graphene oxide is 1000 μm, and the thickness of the γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3 is 1000 μm. x The thickness of the composite active layer II65 is 500 μm;
[0148] The height of the transverse conductive reinforcing rib 7 is 30 mm, the thickness is 10 mm, the thickness of the nickel layer V is 3 μm, the thickness of the titanium layer V is 2 mm, the thickness of the α-PbO2 composite intermediate layer V doped with nickel-coated aluminum powder and graphene oxide is 1000 μm, and the thickness of the γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3 is 1000 μm. x The thickness of the composite active layer V is 500 μm;
[0149] The titanium mesh substrate 81 of the titanium-based manganese dioxide composite mesh plate 8 is TA1 alloy, the mesh long axis is 12 mm, the short axis is 8 mm, the cross-sectional thickness is 6 mm, and the Ta-Nb-SiO x The bottom layer 82 has a thickness of 5 μm and is composed of Mn-Sn-Ti-AgO x The thickness of the bottom layer 83 is 10 μm, the thickness of the α-PbO2 composite intermediate layer VI 84 doped with nickel-coated aluminum powder and graphene oxide is 1000 μm, and the thickness of the γ-MnO2-TiO x The thickness of the composite active layer VI85 is 500 μm;
[0150] A method for preparing a titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning, the specific steps are as follows:
[0151] 1) Titanium mesh-based Ta-Nb-SiO x Preparation of the bottom layer: The titanium mesh substrate was sandblasted and leveled at 600°C, then placed in a 20% NaOH solution, degreased at 80°C for 30 min, and then placed in a 20% oxalic acid solution for boiling activation for 2 h, washed with deionized water, and dried with hot air to obtain a pretreated titanium mesh substrate. xThe precursor liquid was evenly coated on the surface of the pretreated titanium mesh substrate, dried at 100 °C, and then sintered at 700 °C for 10 min. The coating of Ta-Nb-SiO was repeated three times. x The precursor liquid and sintering process, and finally sintered at 600℃ for 1.5h to obtain titanium network-based Ta-Nb-SiO x Bottom layer: the Ta-Nb-SiO x Preparation method of precursor solution: Under ultrasonic and magnetic stirring conditions, tantalum ethoxide, niobium ethoxide and tetraethyl silicate are dissolved in a mixed solvent of isopropanol and n-butanol to obtain Ta-Nb-SiO x precursor fluid;
[0152] 2) Titanium mesh-based Mn-Sn-Ti-AgO x Preparation of the bottom layer: Mn-Sn-Ti-AgO x The precursor liquid is evenly coated on the titanium mesh-based Ta-Nb-SiO x The bottom surface was dried at 100 °C, and then sintered at 300 °C for 10 min. The coating of Mn-Sn-Ti-AgOx precursor liquid and the sintering process were repeated 12 times, and finally sintered at 400 °C for 2.0 h to obtain a titanium mesh-based Mn-Sn-Ti-AgO x Bottom layer: the Mn-Sn-Ti-AgO x The preparation method of the precursor liquid is as follows: manganese nitrate and silver nitrate are dissolved in an ethanol solvent to obtain a manganese-silver mixed solution, dialkyl tin oxide and butyl titanate are dissolved in an n-butanol solvent to obtain a tin-titanium mixed solution, and the manganese-silver mixed solution is added to the tin-titanium mixed solution and stirred to obtain Mn-Sn-Ti-AgO x precursor fluid;
[0153] 3) Assembling the titanium mesh substrate plate: The titanium-clad aluminum conductive beam and the aluminum-copper composite conductive head are welded by aluminum-aluminum friction stir welding to obtain the conductive beam; the titanium mesh base Mn-Sn-Ti-AgO x After cutting, the bottom layer is assembled and welded with the titanium-clad aluminum transition titanium plate, the titanium-clad aluminum substrate III of the cross conductive reinforcement ribs, the titanium-clad aluminum substrate IV of the cross conductive reinforcement ribs, and the titanium-clad aluminum substrate V of the transverse conductive reinforcement ribs to form a titanium mesh base plate substrate, and the titanium-clad aluminum transition titanium plate of the titanium mesh base plate substrate is welded to the bottom end of the conductive crossbeam to obtain a titanium mesh base layer plate;
[0154] The preparation method of the titanium-clad aluminum conductive beam, the titanium-clad aluminum transition titanium plate, the titanium-clad aluminum substrate III of the longitudinal conductive reinforcement ribs, the titanium-clad aluminum substrate IV of the cross conductive reinforcement ribs, or the titanium-clad aluminum substrate V of the transverse conductive reinforcement ribs comprises the following specific steps:
[0155] (a) placing an aluminum alloy rod in a 20% NaOH solution, degreasing it at 60°C for 5 minutes, then washing it with deionized water and dipping it in an alkaline zinc plating solution for 2 minutes, washing it with deionized water and activating it in a 20% HNO3 solution for 10 seconds, dipping it in the alkaline zinc plating solution for a second time for 1 minute, immediately placing it in a chemical nickel plating solution after washing it with deionized water, chemically plating it at 100°C for 60 minutes, washing it with deionized water and drying it to obtain a nickel-clad aluminum composite rod; the alkaline zinc plating solution contains 80g / L ZnO, 300g / L NaOH, 30g / L potassium sodium tartrate, and 5g / L NaNO3; the chemical nickel plating solution contains 45g / L nickel sulfate, 20g / L sodium hypophosphite, 0.1g / L cerium chloride, and 0.5g / L polyethylene glycol 6000; the pH of the chemical nickel plating solution is 5.0;
[0156] (b) The inner wall of the titanium tube is roughened by a wire brush and then degreased, washed with water and placed in a 5% HF solution to remove the oxide film, washed with deionized water and dried with hot air at 80° C. to obtain a pretreated titanium tube;
[0157] (c) placing the nickel-clad aluminum composite rod in a pretreated titanium tube, extruding and drawing the composite rod at a rate of 4 m / min, shearing, hot rolling at a temperature of 400° C., and cooling to room temperature to obtain a titanium-clad aluminum conductive beam, a titanium-clad aluminum transition titanium plate, a titanium-clad aluminum substrate III with longitudinal conductive reinforcement ribs, a titanium-clad aluminum substrate IV with cross conductive reinforcement ribs, or a titanium-clad aluminum substrate V with transverse conductive reinforcement ribs;
[0158] The preparation method of the aluminum-copper composite conductive head comprises the following specific steps:
[0159] The conductive copper rod is placed in a nitric acid solution with a mass concentration of 5%, the oxide film is removed, the rod is washed with deionized water, and then dried. The rod is placed in a hot-dip tin solution and plated at a temperature of 300°C for 5 minutes. The rod is then placed in a die-casting mold at a temperature of 200°C, and the molten aluminum alloy is pressed into the mold and kept warm for 15 minutes. The rod is milled out to the required size by a milling machine to obtain an aluminum-copper composite conductive head. The hot-dip tin solution contains 0.1% Al and the balance is Sn.
[0160] 4) Preparation of α-PbO2 composite intermediate layer doped with nickel-coated aluminum powder and graphene oxide: The titanium mesh base plate substrate of the titanium mesh base layer plate is used as the anode and the stainless steel plate is used as the cathode. The plate is placed in an alkaline composite lead dioxide plating solution at a temperature of 70°C and an anode current density of 3A / dm 2Under the conditions, electroplating for 6 hours forms a composite intermediate layer of α-PbO2 doped with nickel-coated aluminum powder and graphene oxide, and obtains a titanium mesh-based α-PbO2 composite electrode doped with nickel-coated aluminum powder and graphene oxide; the alkaline composite lead dioxide plating solution contains 60g / L lead oxide, 200g / L NaOH, 40g / L lactic acid, 10g / L nickel-coated aluminum powder, and 2g / L graphene oxide;
[0161] The preparation method of the nickel-coated aluminum powder comprises the following specific steps:
[0162] (a) adding flaky aluminum powder degreased by a 10% mass concentration NaOH solution to an electroless copper plating solution, and electroplating for 30 minutes at a temperature of 40° C. to obtain copper-clad aluminum powder; the electroless copper plating solution contains 40 g / L copper sulfate, 80 g / L sodium citrate, 6 g / L sodium hydroxide, 30 ml / L ammonia water, and 5 ml / L formaldehyde solution;
[0163] (b) adding copper-clad aluminum powder to a dilute sulfuric acid solution with a mass concentration of 5% to activate the activated copper-clad aluminum powder, washing the activated copper-clad aluminum powder with deionized water and immediately adding it to a chemical nickel plating solution, and chemically plating it at a temperature of 100° C. for 90 minutes to obtain nickel-clad aluminum powder; the chemical nickel plating solution contains 45 g / L nickel sulfate, 45 g / L sodium hypophosphite, 0.1 g / L cerium chloride, and 0.5 g / L polyethylene glycol 6000, and the pH of the chemical nickel plating solution is 5.0;
[0164] 5)γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 x Preparation of composite active layer: The α-PbO2 composite electrode doped with nickel-coated aluminum powder and graphene oxide on titanium mesh was used as the anode and the titanium mesh plate was used as the cathode. The composite active layer was placed in a manganese sulfate composite plating solution at a temperature of 105°C and an anode current density of 3A / dm 2 Under the conditions of electroplating for 6h, γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 was formed. x The composite active layer is obtained to obtain a titanium-based manganese dioxide gradient composite electrode plate; the manganese sulfate composite plating solution contains 250g / L manganese sulfate, 50g / L titanium sulfate, 150g / L sulfuric acid, 8g / L nano β-MnO2, and 20g / L nano Al2O3;
[0165] The titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning prepared in this embodiment is placed in a zinc electrolyte under the following electrolysis conditions: the electrolyte is 50 g / L Zn 2+ +150g / LH2SO4+800mg / LCl-, solution temperature is 35℃; anode current density is 500A / m 2Compared with the Pb-0.5% Ag alloy anode plate, without changing the electrolytic cell structure, electrolyte composition and operating specifications, the anode life is extended by 3 times, the cell voltage is reduced by more than 16%, the current efficiency is increased by more than 5%, and the cathode product can be 0 # Zinc purity can reach over 95%.
[0166] Example 3: The titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning in this example is basically the same in structure as the titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning in Example 1, except that:
[0167] The titanium-clad aluminum conductive beam 1 has a height of 45 mm and a thickness of 25 mm, a nickel layer Ⅰ12 has a thickness of 3 μm, and a titanium layer Ⅰ13 has a thickness of 2 mm;
[0168] The height of the titanium-clad aluminum transition titanium plate 3 is 120 mm, the thickness is 6 mm, the thickness of the nickel layer II 32 is 2 μmm, and the thickness of the titanium layer II 33 is 1 mm;
[0169] The α-PbO2 composite intermediate layer doped with nickel-coated aluminum powder and graphene oxide has a nickel-coated aluminum powder content of 3wt.%, a graphene oxide content of 0.3wt.% (the particle size of graphene oxide is 50nm), and the remainder is α-PbO2; based on the mass of the nickel-coated aluminum powder being 100%, aluminum (aluminum is a flaky powder with a particle size of 2μm) accounts for 70wt.%;
[0170] γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 x The composite active layer contains 1wt.% of nano-β-MnO2 (the particle size of nano-β-MnO2 is 70nm), 2.5wt.% of nano-Al2O3 (the particle size of nano-Al2O3 is 50nm), 0.3% of Ti, and the balance is γ-MnO2;
[0171] Ta-Nb-SiO x The total molar amount of Ta, Nb and Si in the bottom layer is 100%, the molar amount of Ta accounts for 30%, the molar amount of Nb accounts for 30%, and the molar amount of Si accounts for 40%;
[0172] The total molar amount of Mn, Sn, Ti and Ag in the Mn-Sn-Ti-AgOx bottom layer is 100%, the molar amount of Mn accounts for 55%, the molar amount of Sn accounts for 20%, the molar amount of Ti accounts for 18%, and the molar amount of Ag accounts for 7%;
[0173] The height of the longitudinal conductive reinforcing rib 5 is 20 mm, the thickness is 7 mm, the thickness of the nickel layer III 52 is 1.5 μm, the thickness of the titanium layer III 53 is 1.5 mm, the thickness of the α-PbO2 composite intermediate layer I 54 doped with nickel-coated aluminum powder and graphene oxide is 500 mm, and the thickness of the γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-A12O3 is 500 mm. x The thickness of the composite active layer I55 is 300 mm;
[0174] The height of the cross conductive reinforcement rib 6 is 20 mm, the thickness is 7 mm, the thickness of the nickel layer IV 62 is 1.5 μm, the thickness of the titanium layer IV 63 is 1.5 mm, the thickness of the α-PbO2 composite intermediate layer II 64 doped with nickel-coated aluminum powder and graphene oxide is 500 mm, and the thickness of the γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3 is 500 mm. x The thickness of composite active layer II65 is 300mm;
[0175] The height of the transverse conductive reinforcing rib 7 is 20 mm, the thickness is 7 mm, the thickness of the nickel layer V is 1.5 μm, the thickness of the titanium layer V is 1.5 mm, the thickness of the α-PbO2 composite intermediate layer V doped with nickel-coated aluminum powder and graphene oxide is 500 mm, and the thickness of the γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3 is 500 mm. x The thickness of the composite active layer V is 300 mm;
[0176] The titanium mesh substrate 81 of the titanium-based manganese dioxide composite mesh plate 8 is TA1 alloy, the mesh long axis is 7 mm, the short axis is 5 mm, the cross-sectional thickness is 4 mm, and the Ta-Nb-SiO x The bottom layer 82 has a thickness of 3 μm and is composed of Mn-Sn-Ti-AgO x The thickness of the bottom layer 83 is 6 μm, the thickness of the α-PbO2 composite intermediate layer VI 84 doped with nickel-coated aluminum powder and graphene oxide is 500 μm, and the thickness of the γ-MnO2-TiO x The thickness of the composite active layer VI85 is 300 μm;
[0177] A method for preparing a titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning, the specific steps are as follows:
[0178] 1) Titanium mesh-based Ta-Nb-SiO x Preparation of the bottom layer: The titanium mesh substrate was sandblasted and leveled at 500°C, then placed in a 15% NaOH solution, degreased at 70°C for 20 min, and then placed in a 10% oxalic acid solution for boiling activation for 1.5 h, washed with deionized water, and dried with hot air to obtain a pretreated titanium mesh substrate. xThe precursor liquid was evenly coated on the surface of the pretreated titanium mesh substrate, dried at 90 °C, and then sintered at 500 °C for 8 min. The Ta-Nb-SiO x The precursor liquid and sintering process, and finally sintered at 500℃ for 1h to obtain the titanium network-based Ta-Nb-SiO x Bottom layer: the Ta-Nb-SiO x Preparation method of precursor solution: Under ultrasonic and magnetic stirring conditions, tantalum ethoxide, niobium ethoxide and tetraethyl silicate are dissolved in a mixed solvent of isopropanol and n-butanol to obtain Ta-Nb-SiO x precursor fluid;
[0179] 2) Titanium mesh-based Mn-Sn-Ti-AgO x Preparation of the bottom layer: Mn-Sn-Ti-AgO x The precursor liquid is evenly coated on the titanium mesh-based Ta-Nb-SiO x The bottom surface was dried at 90 °C, and then sintered at 200 °C for 9 min. The coating of Mn-Sn-Ti-AgOx precursor liquid and sintering process were repeated 10 times, and finally sintered at 300 °C for 1.5 h to obtain titanium mesh-based Mn-Sn-Ti-AgO x Bottom layer: the Mn-Sn-Ti-AgO x The preparation method of the precursor liquid is as follows: manganese nitrate and silver nitrate are dissolved in an ethanol solvent to obtain a manganese-silver mixed solution, dialkyl tin oxide and butyl titanate are dissolved in an n-butanol solvent to obtain a tin-titanium mixed solution, and the manganese-silver mixed solution is added to the tin-titanium mixed solution and stirred to obtain Mn-Sn-Ti-AgO x precursor fluid;
[0180] 3) Assembling the titanium mesh substrate plate: The titanium-clad aluminum conductive beam and the aluminum-copper composite conductive head are welded by aluminum-aluminum friction stir welding to obtain the conductive beam; the titanium mesh base Mn-Sn-Ti-AgO x After cutting, the bottom layer is assembled and welded with the titanium-clad aluminum transition titanium plate, the titanium-clad aluminum substrate III of the cross conductive reinforcement ribs, the titanium-clad aluminum substrate IV of the cross conductive reinforcement ribs, and the titanium-clad aluminum substrate V of the transverse conductive reinforcement ribs to form a titanium mesh base plate substrate, and the titanium-clad aluminum transition titanium plate of the titanium mesh base plate substrate is welded to the bottom end of the conductive crossbeam to obtain a titanium mesh base layer plate;
[0181] The preparation method of the titanium-clad aluminum conductive beam, the titanium-clad aluminum transition titanium plate, the titanium-clad aluminum substrate III of the longitudinal conductive reinforcement ribs, the titanium-clad aluminum substrate IV of the cross conductive reinforcement ribs, or the titanium-clad aluminum substrate V of the transverse conductive reinforcement ribs comprises the following specific steps:
[0182] (a) placing an aluminum rod in a 15% NaOH solution, degreasing it at a temperature of 55° C. for 3 minutes, then washing it with deionized water and placing it in an alkaline zinc plating solution for zinc immersion for 1.5 minutes, washing it with deionized water and placing it in a 15% HNO3 solution for activation for 8 seconds, placing it in the alkaline zinc plating solution for secondary zinc immersion for 1 minute, immediately placing it in a chemical nickel plating solution after washing with deionized water, chemically plating it at a temperature of 95° C. for 45 minutes, washing it with deionized water and drying it to obtain a nickel-clad aluminum composite rod; the alkaline zinc plating solution contains 50 g / L ZnO, 250 g / L NaOH, 20 g / L potassium sodium tartrate, and 3 g / L NaNO3; the chemical nickel plating solution contains 30 g / L nickel sulfate, 15 g / L sodium hypophosphite, 0.05 g / L cerium chloride, and 0.2 g / L polyethylene glycol 6000; the pH of the chemical nickel plating solution is 4.5;
[0183] (b) The inner wall of the titanium tube is roughened by a wire brush and then degreased, washed with water and placed in a 3% HF solution to remove the oxide film, washed with deionized water and dried with hot air at 60° C. to obtain a pretreated titanium tube;
[0184] (c) placing the nickel-clad aluminum composite rod in a pretreated titanium tube, extruding and drawing the composite rod at a rate of 3 m / min, shearing, hot rolling at a temperature of 300° C., and cooling to room temperature to obtain a titanium-clad aluminum conductive beam, a titanium-clad aluminum transition titanium plate, a titanium-clad aluminum substrate III with longitudinal conductive reinforcement ribs, a titanium-clad aluminum substrate IV with cross conductive reinforcement ribs, or a titanium-clad aluminum substrate V with transverse conductive reinforcement ribs;
[0185] The preparation method of the aluminum-copper composite conductive head comprises the following specific steps:
[0186] The conductive copper rod is placed in a nitric acid solution with a mass concentration of 3%, the oxide film is removed, the rod is washed with deionized water, and then dried. The rod is placed in a hot-dip tin solution and plated at a temperature of 230°C for 3 minutes. The rod is then placed in a die-casting mold at a temperature of 150°C, molten aluminum is pressed into the mold and kept warm for 10 minutes. The rod is milled out to the required size using a milling machine to obtain an aluminum-copper composite conductive head. The hot-dip tin solution contains 0.05% Al and the remainder is Sn.
[0187] 4) Preparation of α-PbO2 composite intermediate layer doped with nickel-coated aluminum powder and graphene oxide: The titanium mesh base plate substrate of the titanium mesh base layer plate is used as the anode and the stainless steel plate is used as the cathode. The plate is placed in an alkaline composite lead dioxide plating solution at a temperature of 55°C and an anode current density of 1.5A / dm 2Under the conditions, electroplating for 3 hours forms a composite intermediate layer of α-PbO2 doped with nickel-coated aluminum powder and graphene oxide, thereby obtaining a titanium mesh-based α-PbO2 composite electrode doped with nickel-coated aluminum powder and graphene oxide; the alkaline composite lead dioxide plating solution contains 35g / L lead oxide, 150g / L NaOH, 30g / L lactic acid, 6g / L nickel-coated aluminum powder, and 1g / L graphene oxide;
[0188] The preparation method of the nickel-coated aluminum powder comprises the following specific steps:
[0189] (a) adding flaky aluminum powder degreased by a NaOH solution having a mass concentration of 8% to an electroless copper plating solution, and electroplating for 20 minutes at a temperature of 30° C. to obtain copper-clad aluminum powder; the electroless copper plating solution contains 25 g / L copper sulfate, 50 g / L sodium citrate, 4 g / L sodium hydroxide, 20 ml / L ammonia water, and 3 ml / L formaldehyde solution;
[0190] (b) adding copper-clad aluminum powder to a dilute sulfuric acid solution with a mass concentration of 3% to activate the activated copper-clad aluminum powder, washing the activated copper-clad aluminum powder with deionized water and immediately adding it to a chemical nickel plating solution, and chemically plating it at a temperature of 95° C. for 50 minutes to obtain nickel-clad aluminum powder; the chemical nickel plating solution contains 30 g / L nickel sulfate, 30 g / L sodium hypophosphite, 0.05 g / L cerium chloride, and 0.25 g / L polyethylene glycol 6000, and the pH of the chemical nickel plating solution is 4.5;
[0191] 5)γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 x Preparation of composite active layer: The α-PbO2 composite electrode doped with nickel-coated aluminum powder and graphene oxide on titanium mesh was used as the anode and the titanium mesh plate was used as the cathode. The composite active layer was placed in a manganese sulfate composite plating solution at a temperature of 95°C and an anode current density of 1A / dm 2 Under the conditions, γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 was formed by electroplating for 4 h. x The composite active layer is obtained to obtain a titanium-based manganese dioxide gradient composite electrode plate; the manganese sulfate composite plating solution contains 110g / L manganese sulfate, 30g / L titanium sulfate, 60g / L sulfuric acid, 5g / L nano β-MnO2, and 13g / L nano Al2O3;
[0192] The titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning prepared in this embodiment is placed in a zinc electrolyte under the following electrolysis conditions: the electrolyte is 50 g / L Zn 2+ +150g / LH2SO4+800mg / LCl-, solution temperature is 35℃; anode current density is 500A / m 2Compared with the Pb-0.5% Ag alloy anode plate, without changing the electrolytic cell structure, electrolyte composition and operating specifications, the anode life is extended by 3.5 times, the cell voltage is reduced by more than 20%, the current efficiency is increased by more than 6%, and the cathode product can be 0 # Zinc purity can reach over 100%.
[0193] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning, characterized in that: The invention comprises a titanium-clad aluminum conductive beam (1), an aluminum-copper composite conductive head (2), a titanium-clad aluminum transition titanium plate (3) and a manganese dioxide gradient composite electrode plate (4), wherein the aluminum-copper composite conductive head (2) is welded and arranged at one end of the titanium-clad aluminum conductive beam (1), the titanium-clad aluminum transition titanium plate (3) is welded and arranged at the bottom end of the titanium-clad aluminum conductive beam (1), the manganese dioxide gradient composite electrode plate (4) is welded and arranged at the bottom end of the titanium-clad aluminum transition titanium plate (3), and the manganese dioxide gradient composite electrode plate (4) comprises a longitudinal conductive reinforcing rib (5), a cross conductive reinforcing rib (6), a transverse conductive reinforcing rib (7) and a titanium-based manganese dioxide composite mesh plate (8) , longitudinal conductive reinforcing ribs (5) are arranged on both sides of the manganese dioxide gradient composite electrode plate (4), cross conductive reinforcing ribs (6) are arranged on the diagonal of the manganese dioxide gradient composite electrode plate (4), and transverse conductive reinforcing ribs (7) are arranged at the bottom end of the manganese dioxide gradient composite electrode plate (4), and the longitudinal conductive reinforcing ribs (5), the cross conductive reinforcing ribs (6) and the transverse conductive reinforcing ribs (7) form a conductive bracket, and a titanium-based manganese dioxide composite mesh plate (8) is welded in the area formed by the longitudinal conductive reinforcing ribs (5), the cross conductive reinforcing ribs (6) and the transverse conductive reinforcing ribs (7) in the conductive bracket; The longitudinal conductive reinforcing rib (5) comprises, from the inside to the outside, a titanium-coated aluminum substrate III, an α-PbO2 composite intermediate layer I (54) doped with nickel-coated aluminum powder and graphene oxide, a γ-MnO2-TiO2-doped with nano-β-MnO2 and nano-Al2O3, and a x Composite active layer I (55); The cross conductive reinforcing rib (6) comprises, from the inside to the outside, a titanium-coated aluminum substrate IV, an α-PbO2 composite intermediate layer II (64) doped with nickel-coated aluminum powder and graphene oxide, a γ-MnO2-TiO2-doped with nano-β-MnO2 and nano-Al2O3, and a x Composite active layer II (65); The transverse conductive reinforcing rib (7) comprises, from the inside to the outside, a titanium-coated aluminum substrate V, an α-PbO2 composite intermediate layer V doped with nickel-coated aluminum powder and graphene oxide, and a γ-MnO2-TiO2-doped with nano-β-MnO2 and nano-Al2O3. x Composite active layer V; The titanium-based manganese dioxide composite mesh plate (8) comprises, from the inside to the outside, a titanium mesh substrate (81), a Ta-Nb-SiOx bottom layer (82), a Mn-Sn-Ti-AgOx bottom layer (83), an α-PbO2 composite intermediate layer VI doped with nickel-coated aluminum powder and graphene oxide (84) and γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 x Composite active layer VI (85).
2. The titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning according to claim 1, characterized in that: The titanium-clad aluminum conductive beam (1) comprises, from the inside to the outside, an aluminum or aluminum alloy substrate I (11), a nickel layer I (12) and a titanium layer I (13); The aluminum-copper composite conductive head (2) comprises, from the inside to the outside, a copper substrate (23), a tin layer (22), and an aluminum or aluminum alloy layer (21); The titanium-clad aluminum transition titanium plate (3) comprises, from the inside to the outside, an aluminum or aluminum alloy matrix II (31), a nickel layer II (32) and a titanium layer II (33).
3. The titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning according to claim 2, characterized in that: The height of the titanium-clad aluminum conductive beam (1) is 30 to 60 mm, the thickness is 10 to 40 mm, the thickness of the nickel layer I (12) is 1 to 5 μm, and the thickness of the titanium layer I (13) is 1 to 3 mm; The height of the titanium-clad aluminum transition titanium plate (3) is 50-200 mm, the thickness is 4-8 mm, the thickness of the nickel layer II (32) is 0.5-3 μm, and the thickness of the titanium layer II (33) is 0.5-2 mm.
4. The titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning according to claim 1, characterized in that: The α-PbO2 composite intermediate layer doped with nickel-coated aluminum powder and graphene oxide has a nickel-coated aluminum powder content of 1 to 5 wt.%, a graphene oxide content of 0.1 to 0.5 wt.%, and a balance of α-PbO2; based on the mass of the nickel-coated aluminum powder being 100%, aluminum accounts for 60 to 80 wt.%; γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 x The content of nano-β-MnO2 in the composite active layer is 0.1-2wt.%, the content of nano-Al2O3 is 0.5-5wt.%, the content of Ti is 0.1-0.5%, and the balance is γ-MnO2; Ta-Nb-SiO x The total molar amount of Ta, Nb and Si in the bottom layer is 100%, the molar amount of Ta accounts for 20-40%, the molar amount of Nb accounts for 20-40%, and the molar amount of Si accounts for 20-60%; The total molar amount of Mn, Sn, Ti and Ag in the Mn-Sn-Ti-AgOx bottom layer is 100%, the molar amount of Mn accounts for 40-70%, the molar amount of Sn accounts for 15-25%, the molar amount of Ti accounts for 13-25%, and the molar amount of Ag accounts for 2-10%.
5. The titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning according to claim 1 or 4, characterized in that: The titanium-clad aluminum substrate III of the longitudinal conductive reinforcing rib (5) comprises, from the inside to the outside, an aluminum or aluminum alloy substrate III (51), a nickel layer III (52), and a titanium layer III (53); The titanium-clad aluminum substrate IV of the cross-conductive reinforcing rib (6) comprises, from the inside to the outside, an aluminum or aluminum alloy substrate IV (61), a nickel layer IV (62), and a titanium layer IV (63); The titanium-clad aluminum substrate V of the transverse conductive reinforcing rib (7) comprises, from the inside to the outside, an aluminum or aluminum alloy substrate V, a nickel layer V, and a titanium layer V.
6. The titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning according to claim 5, characterized in that: The height of the longitudinal conductive reinforcing rib (5) is 10 to 30 mm, the thickness is 4 to 10 mm, the thickness of the nickel layer III (52) is 0.5 to 3 μm, the thickness of the titanium layer III (53) is 0.5 to 2 mm, the thickness of the α-PbO2 composite intermediate layer I (54) doped with nickel-coated aluminum powder and graphene oxide is 50 to 1000 μm, and the thickness of the γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-A12O3 is 50 to 1000 μm. x The composite active layer I (55) has a thickness of 100 to 500 μm; The height of the cross conductive reinforcing rib (6) is 10 to 30 mm, the thickness is 4 to 10 mm, the thickness of the nickel layer IV (62) is 0.5 to 3 μm, the thickness of the titanium layer IV (63) is 0.5 to 2 mm, and the α-PbO2 composite intermediate layer II doped with nickel-coated aluminum powder and graphene oxide (64) γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3 with a thickness of 50 to 1000 μm x Composite active layer II (65) Thickness: 100 to 500 μm; The height of the transverse conductive reinforcing rib (7) is 10-30 mm, the thickness is 4-10 mm, the thickness of the nickel layer V is 0.5-3 μm, the thickness of the titanium layer V is 0.5-2 mm, the thickness of the α-PbO2 composite intermediate layer V doped with nickel-coated aluminum powder and graphene oxide is 50-1000 μm, and the thickness of the γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3 is 50-1000 μm. x The thickness of the composite active layer V is 100 to 500 μm; The titanium mesh substrate (81) of the titanium-based manganese dioxide composite mesh plate (8) has a mesh long axis of 4 to 12 mm, a short axis of 2 to 8 mm, a cross-sectional thickness of 1 to 6 mm, and a Ta-Nb-SiO x The bottom layer (82) has a thickness of 1 to 5 μm and is composed of Mn-Sn-Ti-AgO x The thickness of the bottom layer (83) is 3 to 10 μm, the thickness of the α-PbO2 composite intermediate layer VI (84) doped with nickel-coated aluminum powder and graphene oxide is 50 to 1000 μm, and the thickness of the γ-MnO2-TiO2 doped with nano-β-MnO2 and nano-Al2O3 is 50 to 1000 μm. x The thickness of the composite active layer VI (85) is 100 to 500 μm.
7. The method for preparing the titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning according to any one of claims 1 to 6, characterized in that: 1) Titanium mesh-based Ta-Nb-SiO x Preparation of the bottom layer: The titanium mesh substrate was subjected to sandblasting, leveling, degreasing and activation treatments to obtain a pretreated titanium mesh substrate. x The precursor liquid is evenly coated on the surface of the pretreated titanium mesh substrate, dried at a temperature of 80-100°C, and then sintered at a temperature of 400-700°C for 5-10 minutes. The coating of Ta-Nb-SiO is repeated 1-3 times. x The precursor liquid and sintering process are finally placed at a temperature of 400-600 ° C for 0.5-1.5 h to obtain a titanium network-based Ta-Nb-SiO x bottom layer; 2) Titanium mesh-based Mn-Sn-Ti-AgO x Preparation of the bottom layer: Mn-Sn-Ti-AgO x The precursor liquid is evenly coated on the titanium mesh-based Ta-Nb-SiO x The surface of the bottom layer is dried at a temperature of 80 to 100 ° C, and then sintered at a temperature of 100 to 300 ° C for 8 to 10 minutes. The coating of the Mn-Sn-Ti-AgOx precursor liquid and the sintering process are repeated 8 to 12 times, and finally sintered at a temperature of 200 to 400 ° C for 1.0 to 2.0 hours to obtain a titanium mesh-based Mn-Sn-Ti-AgO x bottom layer; 3) Assembling the titanium mesh substrate plate: The titanium-clad aluminum conductive beam and the aluminum-copper composite conductive head are welded by aluminum-aluminum friction stir welding to obtain the conductive beam; the titanium mesh base Mn-Sn-Ti-AgO x After cutting, the bottom layer is assembled and welded with the titanium-clad aluminum transition titanium plate, the titanium-clad aluminum substrate III of the cross conductive reinforcement ribs, the titanium-clad aluminum substrate IV of the cross conductive reinforcement ribs, and the titanium-clad aluminum substrate V of the transverse conductive reinforcement ribs to form a titanium mesh base plate substrate, and the titanium-clad aluminum transition titanium plate of the titanium mesh base plate substrate is welded to the bottom end of the conductive crossbeam to obtain a titanium mesh base layer plate; 4) Preparation of α-PbO2 composite intermediate layer doped with nickel-coated aluminum powder and graphene oxide: using the titanium mesh base plate substrate of the titanium mesh base layer plate as the anode and the stainless steel plate as the cathode, electroplating in an alkaline composite lead dioxide plating solution to form an α-PbO2 composite intermediate layer doped with nickel-coated aluminum powder and graphene oxide, thereby obtaining a titanium mesh-based α-PbO2 composite electrode doped with nickel-coated aluminum powder and graphene oxide; the alkaline composite lead dioxide plating solution contains 10-60 g / L lead oxide, 100-200 g / L NaOH, 20-40 g / L lactic acid, 2-10 g / L nickel-coated aluminum powder, and 0.1-2 g / L graphene oxide; 5)γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 x Preparation of composite active layer: Using the titanium mesh-based nickel-doped aluminum powder and graphene oxide α-PbO2 composite electrode as the anode and the titanium mesh plate as the cathode, γ-MnO2-TiO doped with nano-β-MnO2 and nano-Al2O3 was electroplated in a manganese sulfate composite plating solution. x The composite active layer is used to obtain a titanium-based manganese dioxide gradient composite electrode plate; the manganese sulfate composite plating solution contains 50-250g / L manganese sulfate, 10-50g / L titanium sulfate, 40-150g / L sulfuric acid, 2-8g / L nano-β-MnO2, and 5-20g / L nano-Al2O3.
8. The method for preparing the titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning according to claim 7, characterized in that: Step 1) Ta-Nb-SiO x Preparation method of precursor solution: Under ultrasonic and magnetic stirring conditions, tantalum ethoxide, niobium ethoxide and tetraethyl silicate are dissolved in a mixed solvent of isopropanol and n-butanol to obtain Ta-Nb-SiO x precursor fluid; Step 2) Mn-Sn-Ti-AgO x The preparation method of the precursor liquid is as follows: manganese nitrate and silver nitrate are dissolved in an ethanol solvent to obtain a manganese-silver mixed solution, dialkyl tin oxide and butyl titanate are dissolved in an n-butanol solvent to obtain a tin-titanium mixed solution, and the manganese-silver mixed solution is added to the tin-titanium mixed solution and stirred to obtain Mn-Sn-Ti-AgO x Precursor fluid.
9. The method for preparing the titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning according to claim 7, characterized in that: Step 4) The electroplating temperature is 40-70°C and the anode current density is 0.5-3A / dm 2 , the electroplating time is 1 to 6 hours; Step 5) The electroplating temperature is 85-105°C and the anode current density is 0.5-3A / dm 2 , the electroplating time is 3 to 6 hours.
10. The method for preparing the titanium-based manganese dioxide gradient composite electrode plate for non-ferrous metal electrowinning according to claim 7, characterized in that: Step 4) A method for preparing nickel-coated aluminum powder, the specific steps are as follows: Adding degreased flaky aluminum powder into a chemical copper plating solution, and chemically plating for 10 to 30 minutes at a temperature of 20 to 40° C. to obtain copper-clad aluminum powder; the chemical copper plating solution contains 10 to 40 g / L copper sulfate, 30 to 80 g / L sodium citrate, 2 to 6 g / L sodium hydroxide, 10 to 30 ml / L ammonia water, and 0 to 5 ml / L formaldehyde solution; The copper-clad aluminum powder is added into a dilute sulfuric acid solution for activation to obtain activated copper-clad aluminum powder. The activated copper-clad aluminum powder is immediately added into a chemical nickel plating solution after being washed with deionized water. The nickel-clad aluminum powder is chemically plated at a temperature of 90 to 100° C. for 10 to 90 minutes to obtain the nickel-clad aluminum powder. The chemical nickel plating solution contains 15 to 45 g / L nickel sulfate, 5 to 20 g / L sodium hypophosphite, 0.005 to 0.1 g / L cerium chloride, and 0.01 to 0.5 g / L polyethylene glycol 6000, and the pH value of the chemical nickel plating solution is 4.0 to 5.0.